Mechanical Behavior of Marine Soft Soil with Different Water Contents Under Cyclic Loading - Yajun Liu; Heng Zhang; Yindong Sun; Ke Wu; Wenbin Xiao (Journal of Marine Science and Engineering)
This study integrates macroscopic dynamic triaxial tests with microscopic discrete element simulations to comprehensively examine the dynamic deformation characteristics of marine soft soils under cyclic loading. Unlike previous research that typically focuses solely on experimental or numerical methods, this approach combines both techniques to enable a holistic analysis of soil behavior. The dynamic triaxial tests assessed macroscopic responses, including strain evolution and energy dissipation, under varying dynamic stress ratios, confining pressures, and water contents. Concurrently, discrete element simulations uncovered the microscopic mechanisms driving these behaviors, such as particle rearrangement, porosity variations, and shear zone development. The results show that (1) The strain range of marine soft soils increases significantly with higher dynamic stress ratios, confining pressures, and water contents; (2) Cumulative dynamic strain and particle displacement intensify at water contents of 50% and 55%. However, at a water content of 60%, the samples exhibit significant damage characterized by the formation of shear bands throughout the entire specimen; (3) As water content increases, energy dissipation in marine soft soils accelerates under lower confining pressures but increases more gradually under higher confining pressures. This behavior is attributed to enhanced particle packing and reduced pore space at elevated confining pressures. This integrated methodology not only enhances analytical capabilities but also provides valuable engineering insights into the dynamic response of marine soft soils. The findings offer essential guidance for the design and stabilization of marine soft soil infrastructure in coastal urban areas.